ANALISIS STRATEGI KEPUASAN PELANGGAN BERBASIS EXPERIENTIAL MARKETING DAN SUPERIOR QUALITY DALAM MENINGKATKAN LOYALITAS KONSUMEN UMKM KOPI - Rian Andrianto; Bangun Prajadi Cipto; Nano Priyanto; Galang Aji Narotama; Nanang Wahyudi (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to analyze the influence of Superior Quality, Experiential Marketing, and Customer Relationship Management (CRM) on Customer Satisfaction within night-time coffee MSMEs (Micro, Small, and Medium Enterprises) along the Jalan Slamet Riyadi corridor in Surakarta. Amidst a hyper-competitive market and fluctuating monthly revenues, the implementation of appropriate marketing strategies is crucial for the business continuity of these MSMEs. This study employs a quantitative approach using a survey method. A purposive sampling technique was used to select 50 respondents who actively consume coffee in the area. Primary data were collected via Likert-scale questionnaires and analyzed using multiple linear regression. The analysis results indicate that Superior Quality, Experiential Marketing, and CRM—both individually and simultaneously—have a positive and significant impact on Customer Satisfaction. The Experiential Marketing variable makes the dominant contribution to shaping consumer satisfaction perceptions. The coefficient of determination (R²) of 0.672 indicates that 67.2% of the variation in customer satisfaction is explained by these three variables, while the remainder is influenced by factors outside the model. The managerial implications of this study highlight the importance for coffee MSMEs to integrate product quality, the creation of emotional experiences within the shop environment, and personalized customer relationships to reduce customer switching rates.  Keywords: Experiential Marketing, Superior Quality, Customer Relationship Management, Customer Satisfaction, Coffee MSMEs.